Exploring Consumer’s Perception and Their Purchasing Decision For The Companies Involved In CSR Activities - Minhas, Amna Shafiq; Ramsamy, Pariviny; Zhengbing, Zhou (Politeknik Ilmu Pemasyarakatan, 2023)
The current research examined the impact of CSR practices through the qualitative methodology and identified CSR as a very useful tool for marketing and attracting consumers. Likewise, the researchers also explored the factors related to CSR that influence the consumers while adopting or skipping the products. The findings are useful for entrepreneurial ventures where it is explained that business involved in CSR practices outperform their counterparts. Keywords: Corporate Social Responsibility, Consumers, Sustainability, intentions